Chitosan stimulates root hair callose deposition, endomembrane dynamics, and inhibits root hair growth - Drs, Matěj; Krupař, Pavel; Škrabálková, Eliška; Haluška, Samuel; Müller, Karel; Potocká, Andrea; Brejšková, Lucie; Serrano, Natalia; Voxeur, Aline; Vernhettes, Samantha; Ortmannová, Jitka; Caldarescu, George; et al. (Plant, cell & environment, 2025)
Although angiosperm plants generally react to immunity elicitors like chitin or chitosan by the cell wall callose deposition, this response in particular cell types, especially upon chitosan treatment, is not fully understood. Here we show that the growing root hairs (RHs) of Arabidopsis can respond to a mild (0.001%) chitosan treatment by the callose deposition and by a deceleration of the RH growth. We demonstrate that the glucan synthase-like 5/PMR4 is vital for chitosan-induced callose deposition but not for RH growth inhibition. Upon the higher chitosan concentration (0.01%) treatment, RHs do not deposit callose, while growth inhibition is prominent. To understand the molecular and cellular mechanisms underpinning the responses to two chitosan treatments, we analysed early Ca2+ and defence-related signalling, gene expression, cell wall and RH cellular endomembrane modifications. Chitosan-induced callose deposition is also present in the several other plant species, including functionally analogous and evolutionarily only distantly related RH-like structures such as rhizoids of bryophytes. Our results point to the RH callose deposition as a conserved strategy of soil-anchoring plant cells to cope with mild biotic stress. However, high chitosan concentration prominently disturbs RH intracellular dynamics, tip-localised endomembrane compartments, growth and viability, precluding callose deposition.
Keywords: buněčná membrána; Calcium; proteiny huseníčku; Chitosan; gene expression; glukosyltransferasy; signalling; vápník; Arabidopsis Proteins; defence; regulace genové exprese u rostlin; Gene Expression Regulation, Plant; Glucans; Arabidopsis; arabidopsis; kořeny rostlin; Glucosyltransferases; buněčná stěna; glukany; Cell Membrane; cell wall; Plant Roots; chitosan; Cell Wall